2017
DOI: 10.3390/genes8010016
|View full text |Cite
|
Sign up to set email alerts
|

Type 2 Diabetes Susceptibility in the Greek-Cypriot Population: Replication of Associations with TCF7L2, FTO, HHEX, SLC30A8 and IGF2BP2 Polymorphisms

Abstract: Type 2 diabetes (T2D) has been the subject of numerous genetic studies in recent years which revealed associations of the disease with a large number of susceptibility loci. We hereby initiate the evaluation of T2D susceptibility loci in the Greek-Cypriot population by performing a replication case-control study. One thousand and eighteen individuals (528 T2D patients, 490 controls) were genotyped at 21 T2D susceptibility loci, using the allelic discrimination method. Statistically significant associations of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
22
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(22 citation statements)
references
References 65 publications
(100 reference statements)
0
22
0
Order By: Relevance
“…However, to the extent of our knowledge, no GWAS study on the SNP in relation to MS has included the Cypriot population in its study (Baranzini et al, 2009;Beecham et al, 2013; Wellcome Trust Case Control Consortium, Australo-Anglo-American Spondylitis Consortium 2007). Interestingly, studies have suggested that the Cypriot population, though of Caucasian origin, presents with a distinct genetic makeup with significant differences from the northern European populations (Loizidou et al, 2011;Novembre et al, 2008;Votsi et al, 2017). Unique genetic features have been also noted by previous studies, one of which revealed considerable differences between the Cypriot community and the Greek and Turkish communities (Baysal et al, 1992;Hadjisavvas et al, 2010).…”
Section: Discussionmentioning
confidence: 81%
“…However, to the extent of our knowledge, no GWAS study on the SNP in relation to MS has included the Cypriot population in its study (Baranzini et al, 2009;Beecham et al, 2013; Wellcome Trust Case Control Consortium, Australo-Anglo-American Spondylitis Consortium 2007). Interestingly, studies have suggested that the Cypriot population, though of Caucasian origin, presents with a distinct genetic makeup with significant differences from the northern European populations (Loizidou et al, 2011;Novembre et al, 2008;Votsi et al, 2017). Unique genetic features have been also noted by previous studies, one of which revealed considerable differences between the Cypriot community and the Greek and Turkish communities (Baysal et al, 1992;Hadjisavvas et al, 2010).…”
Section: Discussionmentioning
confidence: 81%
“…As stated earlier, some polymorphisms are known to be strongly associated with T2DM (Votsi et al, 2017). Some of these variants are in a nearly close position.…”
Section: Introductionmentioning
confidence: 70%
“…Many studies explain the association of the TCF7L2 gene as one of the causes of the T2DM disease. As revealed by the research of Votsi et al (2017), T2DM is associated with five Single Nucleotide Polymorphism (SNP) statistically in the Greek population. rs7901695 TCF7L2 gene is one of the examples of the associated SNP (Votsi et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…Type 2 diabetes mellitus (T2DM) is a chronic non infectious disease characterized by glucose metabolism disorder caused by dysregulation of multiple genes and environmental factors [1]. The current studies found that more than one gene were associated with T2DM [2,3].…”
Section: Introductionmentioning
confidence: 75%
“…As suggested by Thakkinstian [9], the optimal model was selected through pairwise comparison among genotypes (CC vs TT , OR 1 Discussion T2DM is a disease caused by multiple genes and environmental factors that contribute to insulin resistance or insufficient insulin secretion [15]. SLC30A8 encodes the Zn 2+ transporter ZnT8, which is responsible for the Zinc supply in pancreatic β cells [4], therefore mutations in this gene sequence may affect the function of β cells and thus increase the risk of T2DM.…”
Section: Selection Of Genetic Modelmentioning
confidence: 99%